Impact of Civic Education on Community-Led Crime Control Model in FCT- Abuja, Nigeria - Adebayo, Sule Omeiza; Onyedum, Blessing Ikechi; Azuka, Chukwuma Victoria; Nwachukwu, Emmanuel Lucas (jfpublisher, 2026)
Crime and insecurity remains a critical challenge in Nigeria's Federal Capital Territory (FCT-Abuja), requiring innovative community-based approaches to complement traditional policing strategies. This study examined the impact of civic education on community-led crime control participation in FCT-Abuja. A quantitative survey design was employed with 400 adult residents selected through stratified random sampling across six Area Councils. Data were collected using structured questionnaire with dichotomous responses covering civic education exposure and crime control participation. Chi-square test of independence analyzed the relationship between variables at 0.05 significance level. Findings revealed that 69.6% of respondents had been exposed to civic education programs, while 65.2% participated in community crime control activities. Chi-square analysis (χ² = 56.842, p < 0.001) demonstrated a statistically significant impact of civic education on crime control participation. Residents exposed to civic education were nearly twice as likely to participate in crime control activities (76.5%) compared to unexposed residents (39.3%), representing a 37.2 percentage point difference. Civic education significantly enhances community-led crime control participation in FCT-Abuja. Policymakers should expand civic education coverage, diversify delivery platforms, and ensure sustained programming to strengthen community security capacity across all Area Councils.